Strategi Sosialisasi Pemerintah Daerah Kabupaten Aceh Selatan dalam Pelaksanaan Program Santunan Kematian - Wini Delvia Riski; Nellis Mardhiah (Universitas Teuku Umar, 2021)
This study aims to determine: (1) the socialization strategy, (2) the supporting factors of the socialization strategy, and (3) the inhibiting factors of the socialization strategy. To find out the problems that occur, the researcher uses a qualitative descriptive research method. Data was collected using library techniques, observation, interviews, and documentation for data analysis techniques using descriptive analysis techniques. The study results indicate that: (1) The selection of a good and correct strategy in conducting socialization is the task of the Aceh Privileges and People's Welfare section. The socialization strategy plays a role in realizing the implementation of the death benefit assistance program, which in essence, the community can know and understand death compensation. after that, determine the target in the socialization, then choose the media to be used and the management of socialization. (2) This program supports several parties such as payment partners and the infrastructure used to support this activity. (3) There are obstacles in managing death compensation, namely in terms of education, economy, and social, which causes the majority of the public not to know information about death compensation assistance.